DEVELOPMENT OF TEACHING MATERIAL FOR HIGH ORDER THINKING SKILLS IN READING COMPREHENSION AT STUDENTS MAN 2 MODEL MEDAN - Sherly Hariskha; Risnawaty Risnawaty (Universitas Dharmawangsa, 2022)
RINGKASAN- This study aims to determine the development, validity and effectiveness ofdevelopment of Higher Order Thinking Skills (HOTS) teaching materials in reading comprehension. This research is a research and development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The instrument used is a questionnaire for expert lecturers and students, interviews with teachers, and the results of the last test given to students. The test results from the validator through media design as a whole get very feasible criteria (88.33%) so that teaching materials can be used as teaching materials for students in the learning process. The results of the assessment of English Teaching Materials by experts on the substance of the material as a whole from the aspects that are considered to have received appropriate criteria (90%) so that the Teaching Materials can be used in the learning process.Keyword: Teaching Materials, High Order Thinking Skills, Development, Reading Comprehension.